Measurement of liver and spleen stiffness as complementary methods for assessment of liver fibrosis in autoimmune hepatitis. (2nd December 2020) - Janik, Maciej K.; Kruk, Beata; Szczepankiewicz, Benedykt; Kostrzewa, Konrad; Raszeja‐Wyszomirska, Joanna; Górnicka, Barbara; Lammert, Frank; Milkiewicz, Piotr; Krawczyk, Marcin
Abstract: Background and Aims: Liver stiffness measurements (LSM), commonly performed by transient elastography (TE) or two‐dimensional shear wave elastography (2D‐SWE), are used to quantify liver fibrosis. Active hepatitis, a hallmark of autoimmune hepatitis (AIH), could bias LSM. This bias might be overcome by measurement spleen 2D‐SWE. Here, we compare liver and spleen 2D‐SWE to TE and liver biopsy (LB) in prospectively recruited patients with AIH. Methods: We analysed liver and spleen 2D‐SWE in relation to liver TE in 90 patients treated ≥ 6 months for AIH. Liver and spleen 2D‐SWE were also compared to LB in 63 individuals with AIH. Finally, we evaluated these tools in 220 patients with AIH and during 18 months follow‐up. Results: Liver 2D‐SWE correlated with surrogate markers of active hepatitis (ALT and IgG, both P < .001) but there was no link between spleen 2D‐SWE and ALT. Liver 2D‐SWE, but not spleen 2D‐SWE, was associated with histopathological inflammatory score ( P < .01). When compared to LB, the optimal cut‐offs for detecting cirrhosis by liver and spleen 2D‐SWE were 16.1 kPa (AUROC 0.93) and 29.8 kPa (AUROC 0.95), respectively. In patients with active hepatitis the combined diagnostic approach including liver and spleen 2D‐SWE had significantly better AUROC for detecting cirrhosis than liver 2D‐SWE alone. Conclusions: Liver and spleen 2D‐SWE are reliable complementary methods for the diagnosis of advanced fibrosis in AIH. Spleen 2D‐SWE seems to be less biased by inflammation and could facilitate fibrosis assessment in therapy‐naïve patients or in the presence of active hepatitis.